The Existence of New Direction in Islamic Law Reform Based on The Construction of Ibnu Qayyim al-Jauziyah’s Thought - Asrul Hamid; Dedisyah Putra (Institut Agama Islam Negeri Batusangkar, 2021)
This study examines the Islamic legal thought of Ibn Qayyim al-Jauziyyah in carrying out legal istinbath. Ibn Qayyim al-Jauziyyah is a figure who lived in the XIII century, during which various religious aberrations emerged. The circumstances he was facing significantly influenced some of the ijtihad that he put forward. Therefore, he was well-recognized as a reformer among other scholars of Hanbali school. This research is a character study with a descriptive method using a benefit approach (maqashid al-syariah). The results of this study are about the invitation of Ibn Qayyim al-Jauziyyah to freely exercise ijtihad but in accordance with the Maqashid al-Shari'ah corridor, that is by upholding the principle of maslahah. Because of this, Ibn Qayyim al-Jauziyyah argued that ijtihad can develop according to the times, and the law at his time needed to be more relevant in dealing with and overcoming various circumstances that brought about novel and more complicated problems. This thought emerged as a reaction to the opinion among Muslims who assumed that the door of ijtihad had been closed.